ISLAMIC LIFESTYLE APPLICATIONS AND THE FULFILLMENT OF SPIRITUAL NEEDS AMONG MODERN MUSLIMS: A PHENOMENOLOGICAL RESEARCH - Marzuki Marzuki; Rofii'atul Fitriyyah (Karimiyah: Journal of Islamic Literature and Muslim Society, 2025)
The proliferation of Islamic lifestyle applications has fundamentally transformed the spiritual landscape of contemporary Muslim communities. This phenomenological study investigates how modern Muslims experience and derive spiritual meaning from Islamic mobile applications, with particular emphasis on the fulfillment of multidimensional spiritual needs. Employing an interpretive phenomenological analysis (IPA) framework, this research engaged twelve purposively selected participants from diverse socioeconomic and educational backgrounds in Indonesia. Data were collected through in-depth semi-structured interviews, digital diary recordings, and direct application observation sessions conducted between January and August 2024. Four primary phenomenological themes emerged: (1) the re-ritualization of daily worship through digital mediation; (2) the construction and negotiation of Islamic identity in digital spaces; (3) the democratization of religious authority and knowledge access; and (4) the tension between authentic spirituality and technological superficiality. Findings reveal that Islamic applications effectively fulfill pragmatic-ritual, intellectual-educational, and communal-social spiritual needs, yet simultaneously engender nuanced challenges related to depth of spiritual experience, authenticity of religious practice, and over-reliance on technological mediation. This study contributes an original phenomenological perspective to the growing discourse on digital Islam and technology-mediated religious experience, offering significant implications for application developers, religious educators, and policymakers in Muslim-majority societies.